2013
DOI: 10.1016/j.ydbio.2012.10.012
|View full text |Cite
|
Sign up to set email alerts
|

A gene network that coordinates preplacodal competence and neural crest specification in zebrafish

Abstract: Preplacodal ectoderm (PPE) and neural crest (NC) are specified at the interface of neural and nonneural ectoderm and together contribute to the peripheral nervous system in all vertebrates. Bmp activates early steps for both fates during late blastula stage. Low Bmp activates expression of transcription factors Tfap2a and Tfap2c in the lateral neural plate, thereby specifying neural crest fate. Elevated Bmp establishes preplacodal competence throughout the ventral ectoderm by coinducing Tfap2a, Tfap2c, Foxi1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(89 citation statements)
references
References 48 publications
(100 reference statements)
4
85
0
Order By: Relevance
“…Studies in multiple vertebrates have shown that, once their expression commences in the neural plate border region, these transcription factors engage in a series of mutual cross-regulatory interactions that lead to the stabilization of this regulatory state (Fig. 3C) and ensure their continued expression (Monsoro-Burq et al, 2005;Sato et al, 2005;Nikitina et al, 2008;Bhat et al, 2013).…”
Section: Induction and Formation Of The Neural Plate Bordermentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in multiple vertebrates have shown that, once their expression commences in the neural plate border region, these transcription factors engage in a series of mutual cross-regulatory interactions that lead to the stabilization of this regulatory state (Fig. 3C) and ensure their continued expression (Monsoro-Burq et al, 2005;Sato et al, 2005;Nikitina et al, 2008;Bhat et al, 2013).…”
Section: Induction and Formation Of The Neural Plate Bordermentioning
confidence: 99%
“…For instance, Nikitina and colleagues showed that Tfap2a and Msx1 activate not only each other, but also Zic1 and Pax3/7 (Nikitina et al, 2008). Tfap2a seems to be a key activator of neural plate border specifiers, also being required for the expression of Foxi genes and gata2/3 in zebrafish (Bhat et al, 2013). The more lateral neural plate border genes (Dlx5/6, Gata2/3 and Foxi1/3) also positively regulate each other in multiple positive regulatory loops (McLarren et al, 2003;Matsuo-Takasaki et al, 2005;Kwon et al, 2010; reviewed by Grocott et al, 2012).…”
Section: Induction and Formation Of The Neural Plate Bordermentioning
confidence: 99%
“…The oral ectoderm, which is the presumptive primary mouth, is specified very early and develops from the most anterior portion of a horseshoe shaped preplacodal ectoderm (PPE) [59] [60]. The preplacodal ectoderm region subsequently divides into multiple subdomains, becoming the single oral, and the bilateral nasal, optic, and otic cranial sensory placodes [61].…”
Section: Primary and Secondary Mouthsmentioning
confidence: 99%
“…The formation of segregated placode primordia correlates in time with upregulation of transcription factors specifically expressed in individual or groups of placodes Pieper et al, 2011;Schlosser, 2010;Streit, 2008). Pax2 and Pax8, expressed in the otic and epibranchial placode progenitors (and in lateral line placodes in fish and amphibians), show saltand-pepper expression in chick (Groves and Bronner-Fraser, 2000;Streit, 2002), Xenopus (Pieper et al, 2011;Schlosser and Ahrens, 2004), zebrafish (Bhat et al, 2013;Bhat and Riley, 2011;Hans and Westerfield, 2007;McCarroll et al, 2012; Kozlowski et al, 1997;Bhattacharyya and Bronner, 2013;Breau et al, 2012;Dutta et al, 2005;Harden et al, 2012;Knaut et al, 2005;Kwan et al, 2011;Pieper et al, 2011;Streit, 2002;Whitlock and Westerfield, 2000;Xu et al, 2008) al., 2012) and mice (Ohyama and Groves, 2004). Pax6, a transcription factor expressed in the lens placode, exhibit mosaic expression in zebrafish (Dutta et al, 2005;Hans and Westerfield, 2007).…”
Section: Confrontation Of the Models With Experimental Evidencementioning
confidence: 99%